Congress party of India - "Kochanek, Stanley. A." (Princeton, 1968)
By tracing the path of the Congress Party's development since independence, the author demonstrates the reasons for its success. A postscript deals with the 1967 elections, regarded as a turning point in post-independence Indian politics.
Keywords: Indian National Congress